Hematopoietic stem cell transplantation and gut microbiota: outcomes and use of probiotics, a narrative review - Härter, Jéssica; Mariano da Rocha Silla, Lucia (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2022)
Hematopoietic stem cell transplantation (HSCT) is a complex procedure used to treat several onco-hematological neoplasms, benign hematological diseases, and some types of solid tumors. In recent years, the role of the gut microbiota in HSCT has been studied, revealing that the microbiota has a direct interaction with the immune system and the microbial balance within the body (eubiosis), providing beneficial health effects, and changes in such state result in dysbiosis, which has been associated with several pathological states. The process in which the patient undergoes HSCT can cause microbiota imbalance with reduced diversity, which would be related to negative post-HSCT outcomes, including increased mortality and development of graft-versus-host disease (GVHD). The modulation of the gut microbiota through methods such as the use of probiotics has been explored as an alternative for the recovery and/or maintenance of the gut microbiota.